Reviewing the Federal Employment Equity Act - , (Canadian Woman Studies/les cahiers de la femme, 1992)
- Canadian Labour Congress - Canadian Federation of Business and Professional Women’s Clubs - Saskatchewan Wheat Pool/Grain Services Union - Communications and Electrical Workers of Canada - Manitoba Telephone System